Analisis Faktor Penentu Kemenangan Atlet Cabang Olahraga Pencak Silat Kategori Tanding (Analisis Video Hasil Pertandingan Babak Final Kejuaraan Internasional Kelas Berbeda Usia Dewasa) - Roshita Putri Romadona; Achmad Widodo; Heri Wahyudi; Awang Firmansyah (Indonesian Journal of Kinanthropology (IJOK), 2022)
Background: to find out the techniques that are often used in supporting the winning factor for the competition in the pencak silat sport category. Methods: The method in this study uses a descriptive non-experimental design. Data collection using video analysis via the internet sourced from YouTube, by being analyzed by five people and conducting video validation and data validation. Results: The results showed that the first video resulted in dominant kicks with a total of 12 kicks, the second video with a total of 6 kicks, the third video received a total of 11 kicks and in the fourth video a total of 8 kicks were obtained. Conclusions: Sport is a good physical exercise to maintain health and improve physical fitness. Physical fitness is the body's ability to carry out daily activities without feeling fatigue. Physical fitness is a mandatory requirement that must be possessed by an athlete as the initial foundation in achieving an achievement. From the results of these data, it can be concluded that the technique that is often used by athletes and is a determining factor in the victory of athletes in the pencak silat sport category for international championships for different classes for adults is kicks.